Sosialisasi dan Edukasi Konsumsi Pangan Beragam dan Bergizi di Desa Kekeri - Nazilatus Syiam; Yasyifa Dian Urfina; Muhammad Naim (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
Diverse and nutritious food consumption is key to maintaining public health, preventing malnutrition, and improving quality of life. Desa Kekeri in Gunungsari District, West Lombok, faces challenges related to the low diversity of food consumed by its residents. A socialization and education program on diverse and nutritious food consumption was conducted to enhance the community’s knowledge about the importance of a healthy diet. This activity involved socializing the food groups necessary for the body, practical training on processing nutritious local food, and monitoring the implementation of healthy eating habits. The results showed an increase in the community's knowledge and awareness of balanced diets, as well as an improvement in the utilization of nutritious local foods. Despite challenges such as economic and time constraints, the program successfully encouraged the community to adopt positive changes in their eating habits. The sustainability of this program is expected to improve the nutritional quality and health of the people in Desa Kekeri. Keywords: nutritious food consumption, nutrition education, local food, healthy diet.